Volume reduction of synthetic brine using fertilizer drawn forward osmosis for irrigation: a pilot-scale investigation - El Zayat, Hossam (AUC Knowledge Fountain, 2019)
Due to the growing pressure on the conventional water resources and the increasing population in Egypt, attention has been given to increase the share of seawater desalination in total water resources mix. The most common desalination technology in Egypt is the reverse osmosis (RO) desalination which, beside the production of fresh water, results in large amounts of high salinity brine that is normally being disposed of into the sea. Since the generated brine usually contains traces of chemicals, which have been used for the pretreatment of water, along with a wide range of heavy metals resulting from the corrosion of the pipes, the discharge of the brine into the sea represents a serious environmental challenge if not properly managed. In order to reach an improved overall brine management process, a multitude of research work focused on investigating different techniques in that regard so that the impact on the surrounding environment becomes minimal. A number of parameters have been identified as the key factors which should be considered to reduce the harmful impacts on the environment. This includes both the volume and the chemical composition of the brine, geographical location and available area of the disposal site as well as the capacity of the desalination plant. The volume reduction of the brine could be achieved using different techniques; one of which is the fertilizer drawn forward osmosis (FDFO) process. In that process, RO brine is introduced as the feed solution (FS) while a concentrated fertilizer is used as the draw solution (DS). The process results in further extraction of water from the FS which means a reduction in its volume. The final diluted DS can be used for fertilized irrigation or â€œFertigationâ€; an application that can fill a gap in a country like Egypt with the majority of its water consumption is dedicated for agricultural use. In earlier studies, several fertilizer solutions have been tested as potential DSâ€™s to identify the best performing fertilizers with the highest financial feasibility. In this research, an FDFO process was tested, in both bench-scale and pilot-scale investigations, for the volume reduction of a synthetic brine using a locally manufactured industrial-grade ammonium sulphate (NH4)2SO4 fertilizer as DS and a commercial FO membrane. This work investigated the performance of the tested fertilizer in terms of the resulting water flux at the highest concentration possible of the DS with a fixed concentration of the FS which simulated the brine generated by the RO desalination plants. The aim of the investigation was to perform a techno-economic assessment of the feasibility of using the FDFO process with ammonium sulphate fertilizer as DS to reduce the volume of the brine by extracting water to dilute the DS for a less environmentally challenging management of the brine. In addition to the advantage of reducing the volume of the brine, the resulting diluted DS will be further mixed with the addition of fresh water from the RO plant permeate to reduce its concentration of nutrients to the acceptable levels and produce fertilized water that can be used for fertigation. The bench-scale investigation showed that the process derived an average water flux of 8.09 l/h/m2 which resulted in a volume reduction, and hence a further concentration, of the brine by around 12% using an industrial-grade ammonium sulphate fertilizer as DS which was also diluted by the extracted water by almost 24%. While the pilot-scale investigation showed lower flux, the volume reduction results were consistent with those obtained from the bench-scale investigation. It was concluded that the achieved volume reduction of 12.7% using the proposed process, which requires low energy levels and produces fertilized water for fertigation, was found comparable, in terms of the overall economics of the process, to the recovery rate from brine using an RO process reported in a recent study. Considering the potential applications of the produced fertilized water, these results can be translated into an economically viable solution for the volume reduction of the brine and the production of water for fertigation compared to other reviewed approaches.